Management of trauma-induced coagulopathy (TIC): a synopsis of the updated European trauma guideline - Maegele, Marc (Annals of Research Hospitals; Vol 1 (April 2017): Annals of Research Hospital, 2017)
Uncontrolled hemorrhage and trauma-induced coagulopathy (TIC) are still the major causes for preventable death after trauma (1,2). Approximately one out of four severely injured trauma patients admitted to the hospital is bleeding with variable degrees of laboratory coagulopathy (3). Meanwhile, TIC is recognized as an own clinical entity with substantial impact on outcome and survival after trauma (4). There has been speculation about the potential mechanisms underlying TIC but much of the data continues to be rather correlative than causative with robust links still lacking (5).